Strengthening Sharia Microfinance Regulations And Business Models In Indonesia - Sugeng Sugeng; Annisa Fitria; Adi Nur Rohman; Andre Cardenas Jr. (Jurnal Hukum dan Peradilan, 2024)
This article aims to elaborate on the regulation and model of Islamic microfinance in Indonesia. A clear understanding of the types of microfinance and the business model run by Islamic microfinance is needed to answer the problems faced by this institution. Solid and stable Islamic microfinance institutions serve a critical role in increasing access to loans and business capital for the poor and micro-enterprises. So far, the poor have not been reached by formal financial institution programs. This study employs a normative juridical approach using primary and secondary legal documents. The study results show that the role of the sharia supervisory board and the Cooperatives and SMEs Office has not played an optimal role in ensuring the compliance of microfinance managers with sharia principles and values and prudent microfinance management. The presence of regulations and institutions that guarantee sharia microfinance deposits is needed to protect managed funds and increase public trust.